OC-055 THE INCIDENCE OF EXTRACTION SITE INCISIONAL HERNIA AFTER MINIMALLY INVASIVE COLORECTAL SURGERY: A SYSTEMATIC REVIEW AND META-ANALYSIS. (13th October 2022) - Van Egmond, S; Den Hartog, F; Poelman, M; Menon, A; Kleinrensink, G J; Lange, J; Tanis, P; Deerenberg, E
Abstract: Aim: Minimally invasive colorectal surgery reduces surgical trauma with better preservation of abdominal wall integrity, but the extraction site is still at risk of incisional hernia (IH). This study aimed to determine pooled incidence of IH for each type of extraction site, and to compare IH rates after midline, non-midline and Pfannenstiel extraction. Methods: A systematic review and meta-analysis was conducted using PRISMA guidelines. Single-armed and multiple-armed cohort studies, and randomized controlled trials regarding minimally invasive colorectal surgery were queried from five databases. Outcomes were pooled and compared with random-effects, inverse-variance models. Risk of bias was assessed using the Cochrane ROBINS-I and RoB 2 tools. Results: Thirty-six studies were included, totalling 11, 788 patients. Pooled extraction site incisional hernia (ESIH) rate was 16.0% for midline (n=4081), 9.3% for umbilical (n=2425), 5.2% for transverse (n=3213), 9.4% for paramedian (n=134) and 2.1% for Pfannenstiel (n=1449). ESIH occurred significantly more with midline extraction in comparison to Pfannenstiel (Odds Ratio (OR) 8.4 [3.5;20.0]). Non-midline extraction (transverse and paramedian) showed a significantly lower OR for IH compared to midline extraction (midline and umbilical). Pfannenstiel extraction resulted in significantly lower OR for ESIH compared to midline (OR 0.12 [0.050;0.30]), transverse (OR 0.25 [0.13;0.50]) and umbilical (OR 0.072 [0.033;0.16]) extraction sites. The risks of surgical site infection and surgical site occurrence were not significantly different in any analyses. Conclusions: Specimen extraction through a Pfannenstiel incision is the preferred method in minimally invasive colorectal surgery. In cases where Pfannenstiel extraction is not possible, surgeons should avoid midline specimen extraction.